Food waste digestate composting enhancement by sodium polyacrylate addition: Effects on nitrogen transformation processes and bacterial community dynamics. (1st January 2023) - Fang, Tigao; Wang, Tao; Zhao, Mingxing; Bai, Ling; Deng, Yun; Ruan, Wenquan
Abstract: The influences of sodium polyacrylate (PAAS) at the ratios of 0% (CK), 0.5% (F1), 1.0% (F2), 1.5% (F3), 2.0% (F4) and 2.5% (F5) on nitrogen transformation and bacterial community composition were investigated in the composting of food waste digestate (FWD) and corn straw (CS). PAAS addition increased the thermophilic temperature but had no significant effect on pH values. PAAS exerted significantly effects on the concentration of total nitrogen (TN), ammonia nitrogen (NH4 + -N), nitrite-nitrogen (NO2 − -N) and nitrate-nitrogen (NO3 − -N). The compost product in 1.0% PAAS treatment was more active in absorbing nutrients. Firmicutes (9.40–83.54%), Actinobacteriota (9.98–51.50%), Proteobacteria (0.20–27.87%) and Bacteroidota (0.11–34.69%) were the dominant phyla in FWD composting. Moreover, relative to CK, PAAS promoted the propagation of dominant bacterial phyla Firmicutes with increment of 30.05–102.06% in the thermophilic phase. Kroppenstedtia, Thermobifida and Saccharomonospora were observed to be dominant at the maturing phase and correlated with NH4 + -N, NO2 − -N, TN and NO3 − -N. Therefore, they might be regarded as probable biomarkers symbolic for the maturing phase during FWD composting. The compost product had the highest maturity degree in 1.0% PAAS treatment. These results indicated that PAAS addition improved the maturity and nutrient contents of the compost product as well as altered compost bacterial community dynamics. Graphical abstract: Image 1 Highlights: Composting of FWD with 1.0% PAAS addition formed stable and mature compost. PAAS exerted significantly effects on the concentration of nitrogen (N) forms. PAAS promoted the growth of phyla Firmicutes in the thermophilic phase. Kroppenstedtia, Thermobifida and Saccharomonospora correlated with N conversion.